DBC1 maintains skeletal muscle integrity by enhancing myogenesis and preventing myofibre wasting - Na Liang; Jia He; Jiaqi Yan; Xueying Han; Xiaoqian Zhang; Yamei Niu; Wuga Sha; Jun Li (Wiley, 2024)
Abstract Background Skeletal muscle atrophy, particularly ageing‐related muscular atrophy such as sarcopenia, is a significant health concern. Despite its prevalence, the underlying mechanisms remain poorly understood, and specific approved medications are currently unavailable. Deleted in breast cancer 1 (DBC1) is a well‐known regulator of senescence, metabolism or apoptosis. Recent reports suggest that DBC1 may also potentially regulate muscle function, as mice lacking DBC1 exhibit weakness and limpness. However, the function of DBC1 in skeletal muscle and its associated molecular mechanisms remain unknown, thus prompting the focus of this study. Methods Tibialis anterior (TA) muscle‐specific DBC1 knockdown C57BL/6J male mice were generated through a single injection of 2.00 E + 11 vg of adeno‐associated virus 9 delivering single‐guide RNA for DBC1. Grip strength and endurance were assessed 2 months later, followed by skeletal muscle harvest. Muscle atrophy model was generated by cast immobilization of the mouse hindlimb for 2 weeks. Molecular markers of atrophy were probed in muscles upon termination. Cardiotoxin (CTX) was injected in TA muscles of DBC1 knockdown mice, and muscle regeneration was assessed by immunohistochemistry, quantitative PCR and western blotting. DBC1 knockdown C2C12 cells and myotubes were investigated using immunofluorescence staining, Seahorse, immunohistology, fluorescence‐activated cell sorting and RNA‐sequencing analyses. Results DBC1 knockdown in skeletal muscle of young mice led to signatures of muscle atrophy, including a 28% reduction in muscle grip force (P = 0.023), a 54.4% reduction in running distance (P = 0.002), a 14.3% reduction in muscle mass (P = 0.007) and significantly smaller myofibre cross‐sectional areas (P < 0.0001). DBC1 levels decrease in age‐related or limb immobilization‐induced atrophic mouse muscles and overexpress DBC1‐attenuated atrophic phenotypes in these mice. Muscle regeneration was hampered in mice with CTX‐induced muscle injury by DBC1 knockdown, as evidenced by reductions in myofibre cross‐sectional areas of regenerating myofibres with centralized nuclei (P < 0.0001), percentages of MyoG+ nuclei (P < 0.0001) and fusion index (P < 0.0001). DBC1 transcriptionally regulated mouse double minute 2 (MDM2), which mediated ubiquitination and degradation of forkhead box O3 (FOXO3). Increased FOXO3 proteins hampered myogenesis in DBC1 knockdown satellite cells by compromising around 50% of mitochondrial functions (P < 0.001) and exacerbated atrophy in DBC1 knockdown myofibres by activating the ubiquitin-proteasome and autophagy-lysosome pathways. Conclusions DBC1 is essential in maintaining skeletal muscle integrity by protecting against myofibres wasting and enhancing muscle regeneration via FOXO3. This research highlights the significance of DBC1 for healthy skeletal muscle function and its connection to muscular atrophy.